2007
DOI: 10.1109/tsmcb.2006.880137
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Evolutionary Approach for Optimizing Content-Based Image Indexing Algorithms

Abstract: Optimization of content-based image indexing and retrieval (CBIR) algorithms is a complicated and time-consuming task since each time a parameter of the indexing algorithm is changed, all images in the database should be indexed again. In this paper, a novel evolutionary method called evolutionary group algorithm (EGA) is proposed for complicated time-consuming optimization problems such as finding optimal parameters of content-based image indexing algorithms. In the new evolutionary algorithm, the image datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Due to variety in contents these databases are being used by researchers in various scientific articles of CBIR. Various performance measures like precision, recall, and rank, etc., are calculated to compare the performance of proposed methods with some of already published papers [13,14,16] (see Appendix). Precision is defined in terms of number of relevant images retrieved out of total number of retrieved images considered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to variety in contents these databases are being used by researchers in various scientific articles of CBIR. Various performance measures like precision, recall, and rank, etc., are calculated to compare the performance of proposed methods with some of already published papers [13,14,16] (see Appendix). Precision is defined in terms of number of relevant images retrieved out of total number of retrieved images considered.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have first applied PM1 for CBIR application and analyzed its performance with respect to published literature. It is observed that PM1 results are better than [13,14] and [16]. Tables 1, 2, 4 and 5 shows parameter P wt , P wt_std , P avg , P std , R avg , R std , C avg and C std values for OQWC [14], Subrahmanyam et al [16], PM1 and PM2, respectively.…”
Section: Database Db1 (Corel 1000)mentioning
confidence: 91%
See 1 more Smart Citation
“…proposed an issue for effective and efficient content based image retrieval by presenting a novel indexing and retrieval methodology that combines color, shape and texture, information for the indexing and retrieval [8]. Clustering, particularly fuzzy Cmeans (FCM)-based clustering and its variants, have been extensively used for segmentation due to their simplicity and fast convergence [20] [10] and shown that the performance improvement can be obtained by optimizing the quantization thresholds [11] using genetic algorithm for CBIR application. Texture retrieval is a limb of texture analysis that has attracted wide attention from industries since this is well suited for the identification of products such as ceramic tiles, marble, parquet slabs, etc.…”
Section: Litrature Reviewmentioning
confidence: 99%
“…They are statistical and structural approaches [10]. In structural based texture method, the surface pattern is repetitive such as floor design that contains the same pattern [11]. In statistical texture, the surface pattern is not regularly repetitive such as different flower objects in a picture that normally have similar properties but not exactly the same [12].…”
Section: Texture Featurementioning
confidence: 99%